1978
DOI: 10.1177/002076407802400301
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Cultural and Clinical Determinants of Symptomatology in Obsessional Neurosis

Abstract: Eighty-two obsessional neurotics were studied from a phenomenological viewpoint in order to unmask the clinical and socio-cultural determinants of symptom-choice in this disorder. The form of obsessions and compulsions seemed to be affected primarily by intrinsic factors (age, sex, I.Q.) while their content was affected equally, if not more, by extrinsic factors (religion, locality, social class). Patient's age at the onset of illness seemed to be an extremely relevant factor insofar as it affected both the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Within this premise, it would be worthwhile considering washing as a cultural pathoplasticity of an earlier onset OCD in women. A late onset subgroup of female subjects with OCD has already been documented [4], Com mon reactive factors include pregnancy and puerperal problems [15], Such pathoplasticity has also been observed with the small num ber of Christians in the current study and supported by earlier work [14], suggesting that this group is more likely to have check ing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Within this premise, it would be worthwhile considering washing as a cultural pathoplasticity of an earlier onset OCD in women. A late onset subgroup of female subjects with OCD has already been documented [4], Com mon reactive factors include pregnancy and puerperal problems [15], Such pathoplasticity has also been observed with the small num ber of Christians in the current study and supported by earlier work [14], suggesting that this group is more likely to have check ing.…”
Section: Discussionsupporting
confidence: 86%
“…This could be due to a reluctance by females to seek psychiatric help [12], a greater cultural acceptance of obsessive-com pulsive psychopathology in women [ 13] or an actual unstudied lower morbidity of OCD in women in India. Akhtar et al [14] found that obsessive content is determined more by ex ternal factors (e.g. religion, occupation).…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies in which this has been clearly at tempted. The one major earlier endeavour found that form and content were influenced by various internal and external factors [6], The paucity of studies with large samples has perforce precluded the drawing of conclu sions. This study has basically been a compi lation of data from earlier work and our own experiences, due to which some additional themes have been added.…”
Section: Discussionmentioning
confidence: 99%
“…However they subsequently stress that form should be viewed independently of content. In a later analysis they [6] conclude that form is af fected primarily by intrinsic factors (such as age, sex, IQ) while content is controlled by more extrinsic factors (such as religion, lo cality, social class). Under form could be subsumed ideas, images, impulses, phobias, doubts, fears, convictions and indecision [5,[7][8][9][10][11], The content or ideation includes filth, harm, sex, religion, aggression, inanimate and impersonal objects, philosophy and sin [2,5,12,13], Clinical experience has how ever suggested that these classifications are not adequate and hence we have endea voured in this study to study the form and content of obsessions.…”
Section: Introductionmentioning
confidence: 94%
“…Epidemiological and clinical studies suggest that the most common obsessions include fears of contamination, need for order or symmetry, pathological doubting, and recurrent aggressive or horrific images. The most common compulsive behaviors include washing, checking, counting, ordering, and repeating words or actions [Akhtar et al, 1978;Goodman, 1999;Rasmussen and Tsuang, 1986]. However, in a review of approximately 10 international clinical studies of patients with OCD, Fontenelle et al [2004] found that aggressive and religious obsessions were predominant in Brazilian and Middle Eastern samples, respectively, whereas in other countries, themes of contamination were predominant.…”
Section: Obsessions and Compulsionsmentioning
confidence: 99%